2023
DOI: 10.3390/plants12030481
|View full text |Cite
|
Sign up to set email alerts
|

Copper Uptake and Its Effects on Two Riparian Plant Species, the Native Urtica dioica, and the Invasive Fallopia japonica

Abstract: Copper accumulating in stream sediments can be transported to adjacent riparian habitats by flooding. Although being an essential element for plants, copper is toxic at high concentrations and restricts, among other things, plant growth. Besides copper, invasive plants, such as Fallopia japonica, which are known to be tolerant toward heavy metals, modify riparian habitats. If the tolerance of F. japonica is higher compared to native plants, this could accelerate invasion under high heavy metal stress. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Our results are in accordance with observations reported by Sołtysiak (2020) [44] and Schmitz et al (2023) [73], who tested the effect of Cu contamination by using different concentration treatments on FJ plants. The observations revealed a higher concentration in rhizomes [43,73]. In addition, Vidican et al ( 2023) observed a surpass of Cu notably in roots and leaves of FJ plants in polluted sites in Baia Mare city [50].…”
Section: Macro- Micro-and Trace Elements In Plant Tissuessupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in accordance with observations reported by Sołtysiak (2020) [44] and Schmitz et al (2023) [73], who tested the effect of Cu contamination by using different concentration treatments on FJ plants. The observations revealed a higher concentration in rhizomes [43,73]. In addition, Vidican et al ( 2023) observed a surpass of Cu notably in roots and leaves of FJ plants in polluted sites in Baia Mare city [50].…”
Section: Macro- Micro-and Trace Elements In Plant Tissuessupporting
confidence: 93%
“…The explanation of this surplus can be associated again with the industrialization of the area (for Meris , or) and with agricultural practices (for Bocsig), as Cu is easily accumulated through the utilization of manure as fertilizer or Cu-based fungicides [71,72]. Our results are in accordance with observations reported by Sołtysiak (2020) [44] and Schmitz et al (2023) [73], who tested the effect of Cu contamination by using different concentration treatments on FJ plants. The observations revealed a higher concentration in rhizomes [43,73].…”
Section: Macro- Micro-and Trace Elements In Plant Tissuessupporting
confidence: 91%
See 1 more Smart Citation
“…In SystemLink, aquatic–terrestrial research is conducted at different scales: (A) Ecotoxicological studies at the batch‐scale; (B) The Joint‐Pot Experiment at the site‐scale, in which the effects of soil contamination via flooding can be assessed on soil processes and microbial communities as well as plant parameters (Girardi et al 2022; Schmitz et al 2023). (C) The outdoor Landau Stream Mesocosm Facility (site‐scale) comprises 16 independent concrete stream mesocosms, which can be used to study the aquatic fate and effects of contaminants, and also the potential links to terrestrial ecosystems, for example, via stable isotope analysis.…”
Section: Figmentioning
confidence: 99%
“…2. In SystemLink, aquatic-terrestrial research is conducted at different scales: (A) Ecotoxicological studies at the batch-scale; (B) The Joint-Pot Experiment at the site-scale, in which the effects of soil contamination via flooding can be assessed on soil processes and microbial communities as well as plant parameters (Girardi et al 2022;Schmitz et al 2023). (C) The outdoor Landau Stream Mesocosm Facility (site-scale) comprises 16 independent concrete stream mesocosms, which can be used to study the aquatic fate and effects of contaminants, and also the potential links to terrestrial ecosystems, for example, via stable isotope analysis.…”
Section: Author Contributionmentioning
confidence: 99%